PERBANDINGAN SYARAT SAH NYA PERJANJIAN MENURUT KITAB UNDANG-UNDANG HUKUM PERDATA DAN HUKUM ISLAM - Gunadi (Program Studi Hukum Keluarga Islam, 2025)
This article was written to compare the terms of its agreement valid according to the Book of the Law of Civil Law and Islamic Law. Indonesia is a Constitutional State is therefore in the legal world. Every man is either a citizen or a foreigner is the bearer of rights and obligations that have the right to take legal actions including making agreements with other parties. Agreement which gave birth to the most important source of the engagement. contract and a contract is an agreement or a joint commitment well spoken, gestures, or written between two or more parties that have legal implications which bind to implement them. The contract is very much to be the one to perform a variety of business cooperation. A contract or agreement to be valid and legally binding for the parties who made it. Contract law in Indonesia is in fact very varied due to the different legal systems in each of these countries. This writing mengguunakan normative legal research methods with the comparative study approach. In civil law terms legitimate its agreement including by their ability to make an engagement (bekwaamheid), their licensing as an agreement voluntarily from those who make agreements (toestemming), regarding a case or a particular object (bepaalde onderwerp), as well as their causes (causes) is justified (georloofde oorzak). While the terms legitimate under Islamic law among its agreement with the subject of Engagement (Al›Aqidin), the object of engagement (Mahallul ‹AQD), the purpose of the engagement (Maudhu› ul›Aqd) as well as their Ijab and Kabul (sighat al-›Aqd). Based on the description of the discussion can be drawn a conclusion that the terms of agreement in civil law and Islamic law is almost the same, namely to protect the interests of the parties are mutually entering into a contract. Agreements in Civil Law understood from Western law, while Islamic law is based on Sharia law.